แนวทางการแก้ไขปัญหาความรุนแรงทางการเมืองของไทย - กัปโก ธีร์ดนัย; มาสอน ชัยรัตน์; ชัยเสนา อารดา; อินทร์บึง ลักขณา (Journal of Graduate MCU KhonKaen Campus, 2018)
สาเหตุสำคัญของความรู้สึกเกิดขึ้นจากความต้องการอำนาจและผลประโยชน์วิธีการในการจัดการความคิดที่ว่าในการแก้ปัญหาความต้องการในสิ่งที่จำเป็นต้องมีวิธีการหลายวิธี คำแนะนำในการแก้ไขปัญหาเกี่ยวกับการแก้ไขปัญหาข้อควรระวังในการใช้งาน ยยึดหลักของนิติธรรมนิติรัฐหลักความยุติธรรมความมีคุณธรรมและจริยธรรมโดยความร่วมมือทั้งภาครัฐและผู้มีส่วนเกี่ยวข้องทุกๆฝ่าย Major causes of violence arise from the need for power and benefits. The approach to managing violence is considered appropriate in addressing current violence. Must take several methods. How to integrate Behaviors in the management of violence are the overcoming of the problem of trust in the person is very affect. And how to solve the problem should be used peacefully. Based on the rule of law, the state, the principle of justice. Morality and ethics by cooperation between the government and all stakeholders.